TEACHERS’ PERCEPTIONS TOWARDS THE USE OF ENGLISH TEXTBOOK IN EFL CLASSROOMS - Siti Nurhayati Diniah (Journal of English and Education, 2013)
This paper addresses the study of investigating the teachers’ perceptions towards the use of textbook, their strategies and difficulties in using the textbook in the classroom. The participants of the study were two English teachers at an Islamic senior high school in Cirebon. This was descriptive study using qualitative method as the approach. This study employed three techniques in collecting data: questionnaire, observation and interview. The findings revealed that the teachers perceived positively towards the textbook. The teachers considered that the textbook suited the students’ need, teachers’ need, syllabus and examination. In using the textbook, the teachers used strategies to make an adaptation on textbook by modifying task, adding and omitting the materials. There were two main difficulties faced by teachers; the level of difficulties of the material and limited aids for teaching. The result of the study is expected to broaden teachers’ knowledge about criteria of good textbook and to promote meaningful and communicative purpose for future textbooks. Keywords: perception, textbook, and adapting material